2013
DOI: 10.1590/s1806-37132013000500008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors influencing smoking among medical and non-medical students in Tbilisi, Georgia

Abstract: Objective: Smoking is a serious problem that has a devastating impact on health. The objective of this study was to describe the prevalence of and factors influencing smoking among medical and non-medical students in Tbilisi, Georgia, as well as to determine whether medical education has an impact on smoking. Methods: A cross-sectional study was carried out at Tbilisi State Medical University and Tbilisi State University, both of which are located in Tbilisi, Georgia. A total of 400 4th-year students (200 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
3
12
2
3
Order By: Relevance
“…The results of our large study of university students from 17 low and middle income countries were consistent with a number of previous studies in that overall there was no significant difference in the health risk behaviors of health versus non‐health science students (Maimaiti et al ., ; Chkhaidze et al ., ). This finding is in contrast to some other studies which found fewer health risk behaviors of health versus non‐health science students (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of our large study of university students from 17 low and middle income countries were consistent with a number of previous studies in that overall there was no significant difference in the health risk behaviors of health versus non‐health science students (Maimaiti et al ., ; Chkhaidze et al ., ). This finding is in contrast to some other studies which found fewer health risk behaviors of health versus non‐health science students (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in Tbilisi, Georgia, 49.5% of medical students and 48.0% of non‐medical students were smokers. Of the medical students, 59.5% expressed a willingness to quit smoking, as did 54.2% of the non‐medical students (Chkhaidze et al ., ). Regarding oral health risk behavior in India, Sharda and Shetty () found significantly lower behavior scores for the non‐medical students than for the para‐medical and medical categories.…”
Section: Introductionmentioning
confidence: 97%
“…Em diversos estudos constatou-se que para o cigarro, o sexo masculino apresentou predominância ao uso em relação ao feminino (ZAITUNE et al, 2012;CHKHAIDZE et al, 2013;MALTA et al, 2015). Assim como no narguilé, o sexo masculino apresenta maior frequência de uso (AL-NAGGAR & SAGUIR, 2011;SABAHY et al, 2011;GRANT et al, 2014 Nesta pesquisa a idade dos entrevistados variou de 17 a 56 anos, com média obtida foi de 22,42 ± 5,81 anos.…”
Section: Dados Sociodemográfico E Tabagismounclassified
“…Finally, there was a study done in Georgia "Prevalence of and factors influencing smoking among medical and non-medical students in Tbilisi, Georgia s" which found of the sample as a whole, 48.75% were identified as smokers and 51.25% were identified as nonsmokers [10].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%